Invasion success and impact of an invasive fish, round goby, in Great Lakes tributaries. Issue 2 (26th September 2012) - Kornis, Matthew S.; Sharma, Sapna; Jake Vander Zanden, M.; Ricciardi, Anthony
Abstract Aim Environmental and biological characteristics interact in complex ways to determine ecosystem susceptibility to invasive species, and a greater understanding of their relative roles in invader spread and impact is needed. We evaluated relationships between environmental characteristics, biodiversity of indigenous species, and the abundance and ecological impact of an invasive fish, round goby (Neogobius melanostomus). Location Tributaries to Lake Michigan, WI, USA. Methods We assessed the distribution and abundance of round gobies and native fishes in tributaries via electrofishing. We compared fish community composition and diversity in streams with (n = 30) and without (n = 52) round gobies and examined how trends in round goby abundance from 2007 to 2010 correlated with changes in abundance of five native benthic fishes. We used redundancy analysis to determine how indigenous stream communities related to environmental characteristics and round goby abundance. Results Round goby abundance was best explained by environmental characteristics, with watershed area and temperature explaining 22.4% of the variation. Species richness and Shannon diversity only explained 6.9% of the variation in round goby abundance and only an additional 2.3% after considering environmental characteristics. Round goby abundance was not a significant predictor of fish community composition, which was best explained by seven environmental variables (30.3% of the variation). Invaded communities had significantly higher indigenous species richness than uninvaded communities (8.38 vs. 6.54). Round goby abundance was low compared with estimates from other studies, but showed an increasing trend in many tributaries (average 10.8‐fold increase from 2007 to 2010). Surprisingly, there were no temporal trends in native benthic fish abundance despite increases in round goby abundance. Main conclusions Environmental characteristics favouring high fish diversity (e.g. resource availability and warm water temperature) were positively associated with round goby abundance. However, round goby density and impact are relatively low in most tributaries at present, emphasizing the importance of considering heterogeneity in an invader's abundance when assessing invasion success.